Muslim-guide : using augmented reality and intuitive features for determining qibla direction and prayer times - Ng Ah Ngan, Mike Christian Tien Tsong (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Everyday, more than a billion of Muslims in the world face the Ka’bah in Mecca five times as they perform their daily prayers. The direction towards the sacred Ka’bah is called qibla. While before, mainly when travelling around the world, people used conventional methods such as stick to see the shadow in order to know the prayer times and qibla direction, nowadays, various mobile and web applications exist to accomplish similar tasks. However, such applications requires huge location databases, requires human intervention to calculate current location, displays relative directions rather than absolute directions or use various geographical notations and terminologies that requires mental effort or reduces users’ learnability. Therefore, this study investigated the potential of using Augmented Reality, which is defined as the latest advancements of Human Computer Interaction technology and context-aware computing environment to improve the mental model design in mobile-based qibla applications.This study offered a new method of visualizing spatial information by overlaying multiple intuitive features onto the live streaming from the mobile’s camera to provide cognitive advantages and enhance perceptual guidance. Finally, a proposed Location based application called “Muslim Guide” was developed to demonstrate its usability and reliability compared to current qibla applications.